Gluten-free pastry products: compliance with the Portuguese Integrated Strategy for the Promotion of Healthy Eating (EIPAS) - Capelas, R. (2020)
Introduction: Over the last years, gluten-free foods market has expanded rapidly, because not only there is an increase in the number of people diagnosed with coeliac disease, but also due to the consumer’s perception, since they consider that these foods are a healthier option. Objectives: (i) To determine the total fat and salt content of gluten-free pastry products; and (ii) To analyse the compliance with the recommendations of the Portuguese Integrated Strategy for the Promotion of Healthy Eating (EIPAS). Methodology: During 2019, 12 gluten-free pastry products were acquired from the major stores in Portugal. Then, total fat content (acid hydrolysis followed by Soxhlet extraction with petroleum ether) and salt content (Charpentier-Volhard titration method) were determined. Also, the contribution of these foods for the Daily Reference Intake (70 and 6 g/day for fat and salt, respectively) of these components was evaluated. Main findings: Total fat content varied between 7.05 and 28.4 g/100 g. All the analysed gluten-free pastry products had a fat content higher than 15 g/100 g, except crackers (14.1 g/100 g) and ladyfingers (7.05 g/100 g). However, one of the samples with the lowest content of fat was the sample with the highest salt content (1.22 g/100 g). According to EIPAS, it is intended to achieve a salt content lower than 0.3 g/100 g. In this study, 83% of the selected gluten-free products have a salt content higher than 0.3 g/100 g. Conclusion: Similarly to what happens to pastry products with gluten, gluten-free products have a high content of fat and salt. Therefore, the reformulation of these foods, which is a desired goal by the national and international organizations, to offer healthier options to consumers, should be targeted for gluten-free products.